Technology Acceptance in Education - Teo, Timothy; SpringerLink (Online service) (Rotterdam : SensePublishers, 2011)
Technology acceptance can be defined as a user$1 (Bs willingness to employ technology for the tasks it is designed to support. Over the years, acceptance researchers have become more interested in understanding the factors influencing the adoption of technologies in various settings. From the literature, much research has been done to understand technology acceptance in the business contexts. This is understandable, given the close relationship between the appropriate uses of technology and profit margin. In most of the acceptance studies, researchers have sought to identify and understand the forces that shape users$1 (Bacceptance so as to influence the design and implementation process in ways to avoid or minimize resistance or rejection when users interact with technology. Traditionally, it has been observed that developers and procurers of technological resources could rely on authority to ensure that technology was used, which is true in many industrial and organizational contexts. However, with the increasing demands for educational applications of information technology and changing working practices, there is s need to re-examine user acceptance issues as they emerge within and outside of the contexts in which technology was implemented. This is true in the education milieu where teachers exercise the autonomy to decide on what and how technology will be used for teaching and learning purposes. Although they are guided by national and local policies to use technology in the classrooms, teachers spent much of their planning time to consider how technology could be harnessed for effective lesson delivery and assessment to be conducted. These circumstances have provided the impetus for researchers to study technology acceptance in educational settings. Although these studies have typically involved students and teachers as participants, their findings have far-reaching implications for school leaders, policy makers, and other stakeholders. The book is a critical and specialized source that describes recent research on technology acceptance in education represented by educators and researchers from around the world such as Australia, Belgium, China, Hong Kong, Malaysia, Singapore, United Kingdom, and United States of America.s
Keywords: Education; Education; Educational Technology